(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current situation of stress, anxiety, and depression among mothers with children aged 0–5 years in Viet Hung commune, Dong Anh district, Hanoi. Methods: A cross-sectional study using the Vietnamese version of the Depression, Anxiety and Stress Scale (DASS-21) was conducted on 104 mothers with children aged 0–5 years in Viet Hung commune, Dong Anh district, Hanoi. Results: A total of 21.2% of mothers showed signs of stress, with mild stress accounting for 63.7%, moderate stress 22.6%, and severe stress 13.7%. The prevalence of anxiety was 76.9%, with moderate anxiety being the most common (58.8%), followed by severe/very severe (28.7%) and mild anxiety (12.5%). The prevalence of depression was 72.1%, with moderate depression accounting for 52.0%, mild depression 42.7%, and severe/very severe depression 5.3%. Conclusion: The study results showed that mental health disorders among mothers with young children in Viet Hung commune remain an issue that needs attention. Therefore, appropriate and timely psychological interventions are needed to improve the quality of life for both mothers and children.